OPTIMISATION OF GOVERNANCE AND GCG IN STATE-OWNED ENTERPRISES: A LITERATURE REVIEW ON TRANSPARENCY, ACCOUNTABILITY, AND ERADICATION OF CORRUPTION PRACTICES - Agustinus Nugroho Jati; Gunawan Widjaja; Dyah Ersita Yustanti (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to systematically examine how optimising governance and implementing Good Corporate Governance (GCG) principles can serve as an effective strategy in eradicating corruption practices in State-Owned Enterprises (SOEs). Through a literature review approach, this study outlines the role of transparency and accountability as key pillars in sound SOE governance, while also analysing the obstacles and challenges in their implementation. Furthermore, this study explores how strengthening internal and external supervisory institutions, implementing digital governance technology, and transforming organisational culture play an important role in closing corruption loopholes. The results of the study show that optimising GCG not only improves the performance of SOEs but also serves as a strategic instrument for building integrity, strengthening accountability, and promoting transparency in a sustainable manner. The implications of this study encourage policymakers and SOE management to strengthen the governance framework with the support of regulations, technology, and multi-stakeholder participation in order to realise clean and professional SOEs.